Pengelolaan Bengkel Teknik Mekatronika SMK Negeri 2 Sukoharjo Tahun 2016 - Mulyanto, Eko, Dr. Sumardi, M.Si, Dr. Suyatmini, M.Si (2016)
The purpose of this study is (1). Describe the procurement of equipment and materials in the workshop practices Mechatronics SMK Negeri 2 Sukoharjo. (2). Describing the use of tools and materials in the workshop practices Mechatronics SMK Negeri 2 Sukoharjo. (3). Describe Maintenance of tools and materials in the workshop practices Mechatronics SMK Negeri 2 Sukoharjo. The research was conducted at SMK Negeri 2 Sukoharjo. This type of research is qualitative research with a naturalistic approach. The technique of collecting data through observation, interviews and documentation. The study design using the design ethnography. The informant as a resource is the principal, vice-principal fields of infrastructure, head of engineering packages mechatronics and mechatronic engineering practice teacher. The collected data was then analyzed by means of data reduction, presentation / display data and drawing conclusions / verification. Testing the validity of using, triangulation source and triangulation techniques. Research result are showing that the procurement of equipment and materials may gradually be met by the school. The Central Government provides financial assistance, in the form of deconcentration fund is realized through the proposal and verification proposal. The use of mechatronic engineering workshop solely for practical learning process to improve students' skills. Program activities in mechatronic engineering workshop include the provision, use and maintenance of tools and materials. Based on the findings of this research for the procurement of mechatronic engineering workshop equipment is good, need to conduct equipment maintenance technicians and are designed to be held periodically or periodic maintenance. Similarly, for an inventory of equipment and materials showed the results have not oftimal due to the lack of space for storage of tools and materials. Keywords: management, procurement, use and maintenance materials